Diatom succession dynamics controlled by multiple forces in a subtropical reservoir in southern China. (10th November 2018) - Lei, Yuanda; Du, Xiaoqin; Wang, Yasu; Chen, Qiuju; Tang, Hongqu; Jiang, Shijun
Abstract: Investigating how freshwater ecosystems respond to multiple environmental stresses provides important references for catchment management and model prediction. Here we compared the pre- and post-impoundment diatom and geochemical records from the subtropical Liuxihe Reservoir in South China, attempting to demonstrate the diatom succession dynamics during the reservoir maturation process under climate-human interaction. The Nonmetric Multidimensional Scaling (NMDS) and Redundancy Analysis (RDA) revealed a clear trajectory of diatom assemblage succession in the context of multiple stressors on Liuxihe Reservoir. Right after damming (1956–1958), the reservoir underwent a rapid shift from lotic into lentic conditions with abrupt decreases in sediment grain size and magnetic susceptibility, and increases in diatom planktonic/benthic (P/B) ratios and valve concentrations. The reservoir then entered a lengthy, lake-forming process with decreasing C/N ratios and δ 13 C values. This process was interrupted by a combination of climate changes and anthropogenic activities since the 1990s, and the resulting limnological conditions appeared to favor the planktonic Cyclotella hubeiana and Discostella stelligera . In the long term, the diatom biomass seemed to respond sensitively to hydrodynamic regulations in this artificially hydraulic-controlled reservoir ecosystem.